2019
DOI: 10.1101/855098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wounding and insect feeding trigger two independent MAPK pathways with distinct regulation and kinetics

Abstract: AbstractWounding is caused by abiotic and biotic factors and triggers complex short- and long-term responses at the local and systemic level. These responses are under the control of complex signaling pathways, which are still poorly understood. Here, we show that the rapid activation of MKK4/5-MPK3/6 by wounding is independent of jasmonic acid (JA) signaling and that, contrary to what happens in tobacco, this fast module does not control wound-triggered JA accumulation in Arab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…40 MAPKs have four clades, among which MPK3 and MPK6 belong to clade A. 40 The plant MAPK cascade influences the expression of downstream genes by passing stress signals generated during in abiotic stress. 41,42 We mapped DPPs to the MAPK signaling pathway according to the KEGG database and found that MKK4/5 and MPK3/6 cascade proteins were increased in the UVB group according to phosphoproteomic data (Figure 8, Table S3).…”
Section: Mapk Signaling Pathway and Activated Hyperosmotic Response W...mentioning
confidence: 99%
See 1 more Smart Citation
“…40 MAPKs have four clades, among which MPK3 and MPK6 belong to clade A. 40 The plant MAPK cascade influences the expression of downstream genes by passing stress signals generated during in abiotic stress. 41,42 We mapped DPPs to the MAPK signaling pathway according to the KEGG database and found that MKK4/5 and MPK3/6 cascade proteins were increased in the UVB group according to phosphoproteomic data (Figure 8, Table S3).…”
Section: Mapk Signaling Pathway and Activated Hyperosmotic Response W...mentioning
confidence: 99%
“…39 When wounding does occur, plants respond to this damage by triggering the MAPK signaling pathway. 40 MAPKs have four clades, among which MPK3 and MPK6 belong to clade A. 40 The plant MAPK cascade influences the expression of downstream genes by passing stress signals generated during in abiotic stress.…”
Section: Mapk Signaling Pathway and Activated Hyperosmotic Response W...mentioning
confidence: 99%